Three-Dimensional Reconstruction of Complex Defects in Thin Steel Strips with the Imaging Method of Magnetic Field Distortion. Issue 6 (2nd November 2021) - Li, Hengtao; Liu, Xiucheng; Zhang, Jiaying; Wang, Chang; Wu, Bin; He, Cunfu
ABSTRACT: In the study, the three-dimensional (3D) morphology of defects in thin steel strips with a thickness of 0.8 mm was determined with the imaging method of magnetic field distortion (MFD). First, MFD imaging of through-wall defects and wall-thinning defects in the samples collected from inline products was performed in our laboratory. The actual profiles of the defects were measured with a digital microscope. Second, MFD imaging results were compared with the actual shapes of the defects in order to develop a proper 3D reconstruction method of complex defects. Finally, the analysis results demonstrated that the high reconstruction accuracy of opening contours of complex defects could be realized with the carefully selected threshold value of MFD-induced voltage amplitude. The good linear dependency of MFD-induced voltage amplitude on the depth of complex wall-thinning defects was confirmed. Therefore, MFD imaging method is a promising method for accurately reconstructing 3D shape of complex wall-thinning defects in thin steel strips.